Nicho trófico e redes de interação de morcegos frugívoros na província cárstica do Alto São Francisco - Genelhú, Sebastião Maximiano Corrêa (2022)
Bats perform several trophic roles, having a fundamental role in the functioning of the ecosystem, mainly due to their high diversity and abundance in tropical regions. These functions have been studied in recent decades, especially frugivory and seed dispersal, as they are considered essential interactions for the preservation of ecological and evolutionary dynamics. Two ways of studying this relationship are trophic niche analysis and interaction networks. Trophic niche is related to the diet of bats and is studied by collecting fecal samples. Interaction networks concerns metrics capable of expressing a set of interactions between species in a community. In this sense, the present dissertation is divided into two chapters, the first seeking to investigate the diversity of the diet of fruit bats in a karst region in Minas Gerais, and the second chapter testing which aspects of taxonomic, functional and phylogenetic diversity of bats influence the structure of the interaction networks between bat-plants in the collected areas. Six field expeditions were carried out over a year, between February 2020 and April 2021, covering the dry and rainy seasons, including 12 sampling points. The fecal samples collected during the handling of the animals in the net, and in the cloth bags, were placed in plastic microtubules containing 70% alcohol, labeled, and then taken to the laboratory for analysis under a stereomicroscope. The results found suggest that ecologically similar bat species occupy different trophic niches, ensuring coexistence mediated by resource partition, and that diversity indices can affect differently the properties of the interaction network.